Molecular transitions in early progenitors during human cord blood hematopoiesis. Issue 3 (15th March 2018) - Zheng, Shiwei; Papalexi, Efthymia; Butler, Andrew; Stephenson, William; Satija, Rahul
Abstract: Hematopoietic stem cells (HSCs) give rise to diverse cell types in the blood system, yet our molecular understanding of the early trajectories that generate this enormous diversity in humans remains incomplete. Here, we leverage Drop‐seq, a massively parallel single‐cell RNA sequencing (scRNA‐seq) approach, to individually profile 20, 000 progenitor cells from human cord blood, without prior enrichment or depletion for individual lineages based on surface markers. Our data reveal a transcriptional compendium of progenitor states in human cord blood, representing four committed lineages downstream from HSC, alongside the transcriptional dynamics underlying fate commitment. We identify intermediate stages that simultaneously co‐express "primed" programs for multiple downstream lineages, and also observe striking heterogeneity in the early molecular transitions between myeloid subsets. Integrating our data with a recently published scRNA‐seq dataset from human bone marrow, we illustrate the molecular similarity between these two commonly used systems and further explore the chromatin dynamics of "primed" transcriptional programs based on ATAC‐seq. Finally, we demonstrate that Drop‐seq data can be utilized to identify new heterogeneous surface markers of cell state that correlate with functional output. Synopsis: Single‐cell transcriptome profiling of hematopoietic progenitors collected from human cord blood provides molecular evidence for multi‐lineage transcriptomic priming in early progenitors, which correlates with epigenetic state, surface marker expression, and functional output. Unsupervised reconstruction of transcriptomic cell states in human CD34 + hematopoietic progenitors from cord blood is performed using Drop‐seq. "Primed" and " de novo " programs that accompany specification into four downstream lineages are identified. Integration of cord blood and bone marrow single cell datasets reveals strong conservation of molecular programs. Heterogeneous surface markers are identified within early lymphoid‐primed multipotent progenitors (LMPPs) and their expression correlates with transcriptomic state and functional potential. Abstract : Single‐cell transcriptome profiling of hematopoietic progenitors collected from human cord blood provides molecular evidence for multi‐lineage transcriptomic priming in early progenitors, which correlates with epigenetic state, surface marker expression, and functional output.